1994
DOI: 10.1111/j.1528-1157.1994.tb02434.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and EEG Asymmetries in Juvenile Myoclonic Epilepsy

Abstract: We reviewed records of 85 patients with juvenile myoclonic epilepsy (JME) for significant asymmetries in clinical seizures or the EEG. We noted asymmetries in 26 of 85 patients (30.6%). Only 2 patients had both clinical and EEG asymmetries; 12 had clinical asymmetries and 12 had EEG asymmetries exclusively. Analysis of patients with and without asymmetries showed no statistically significant differences in comparisons of sex, age at seizure onset, family history of epilepsy, seizure type, or response to treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
2
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 8 publications
3
89
2
5
Order By: Relevance
“…Epileptiform EEG asymmetries in juvenile myoclonic epilepsy are frequent and various rates are reported in the literature: 16.5% 4,6 , 38.1% 12 and 72.7% 8 . In our study, more than half the patients, namely 57.1%, had EEG asymmetric features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epileptiform EEG asymmetries in juvenile myoclonic epilepsy are frequent and various rates are reported in the literature: 16.5% 4,6 , 38.1% 12 and 72.7% 8 . In our study, more than half the patients, namely 57.1%, had EEG asymmetric features.…”
Section: Discussionmentioning
confidence: 99%
“…Electroencephalogram asymmetries are not uncommon in JME, varying between 16.5 to 73% in previous studies [6][7][8][9] . These asymmetric features can contribute to the misdiagnosis of this syndrome and lead to treatment with carbamazepine or oxcarbazepine that may have an aggravating effect particularly on absences and https://www.cambridge.org/core/terms.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The results as to the lateralized abnormalities of this series are similar to those reported by Panayiotopoulos et al 5 and Montalenti et al 16 . Lancman et al 19 reported that the average time of delay for the establishment of diagnosis in patients with asymmetry was greater than in those with symmetric alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of detecting epileptiform activity was also 100% in untreated compared to 63% in JME patients on treatment 21 . Several studies have reported focal EEG abnormalities in 16% to 54% of JME patients 22,23 . Most studies do not define asymmetry or focal abnormality very clearly.…”
mentioning
confidence: 99%